Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Ways to Achieve The Dimensions of Sustainable Development at The Yemeni University of Saada and its Importance; From The Point of View of Academic Leaders and Faculty Working in itMr. Abdul Rahman Muhammad Dahesh, Co-Prof. Abdul-Jabbar Al-Tayyib Amin2. The reality of the practice of digital citizenship by secondary school leaders in Riyadh and the requirements for its activation in the light of the European experience from their point of viewMrs. Afaf Othman Al-Ghamdi, Co-Prof. Hessa Saad Al-Arifi3. Transforming traditional universities in The Kingdom of Saudi Arabia into smart universities  in the light of employing artificial intelligenceMrs. Rehab Saud Maghrabi4. The Degree Of the First three Grades Teachers Practice Of the Twenty-First Century Skills From Their PerspectivesMrs. Sawsan Ramzi Abdullah Abu Hilal, Co-Prof. Othman Nasser Mansour5. Anticipating the Future of Green Human Resource Management in Riyadh's Governmental Middle Schools Using the Delphi MethodMrs. Fatmah Hameed Altowairqi6. Building the motivations towards E-Shopping Scale among Umm Al-Qura University studentsMrs. Tahani Qablan Al-Omayri7. The Application of Institutional Excellence Standards in Bethlehem’s Private Schools  Based on Malcolm Baldrige’s ModelMrs. Shireen Elias Awad, Prof. Mahmoud A. Abu Samra
Keywords: Journal of Educational and Psychological Sciences